Writing poems - Boisseau, Michelle , 1955-; Mann, Randall; Wallace, Robert , 1932- (Pearson Longman, 2008)
The gold standard of poetry writing books, "Writing Poems, 7/e" is a comprehensive, easy-to-use guide that will help aspiring poets to create meaningful works